General Overview of the State of the Banking System of the Republic of Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2023)
The banking system of the Republic of Uzbekistan is currently experiencing dynamic development and growth. It has a fairly high level of concentration, which is due to a small number of large banks that control most of the bank's assets and loan portfolio. At the same time, since 2017, active work has begun on reforming the banking system, aimed at increasing competition and reducing this concentration.